2017
DOI: 10.3892/mmr.2017.6197
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR-30b as an oncogene in renal cell carcinoma

Abstract: microRNAs (miRs) have been investigated as a novel class of regulators of cellular processes, including proliferation, apoptosis and metabolism. In particular, miR‑30b has been demonstrated to be deregulated in certain types of cancer, including lung, colorectal and gastric cancer. Previous studies of miR‑30b in renal clear cell carcinoma demonstrated that the expression level of miR‑30b was associated with distant metastasis. However, the function of miR‑30b in renal cell carcinoma (RCC) remained to be elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…More specifically, previous findings suggest that knockdown of Proteolipid protein 2 can inhibit cell proliferation, migration and invasion of glioma with decrease of MMP-2 and MMP-9 [35]. Furthermore, elevated expression of miR-30b found in renal cell carcinoma (RCC) cells was demonstrated to promote RCC cell proliferation, invasion and migration but inhibit cell apoptosis [36]. In line with our results, accumulating evidences show that RECK can inhibit tumor angiogenesis, migration, invasion and metastasis in glioma [37–39].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, previous findings suggest that knockdown of Proteolipid protein 2 can inhibit cell proliferation, migration and invasion of glioma with decrease of MMP-2 and MMP-9 [35]. Furthermore, elevated expression of miR-30b found in renal cell carcinoma (RCC) cells was demonstrated to promote RCC cell proliferation, invasion and migration but inhibit cell apoptosis [36]. In line with our results, accumulating evidences show that RECK can inhibit tumor angiogenesis, migration, invasion and metastasis in glioma [37–39].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found aberrantly lower‐expression of miRNAs in colorectal tissues in contrast with normal tissues (Akao, Nakagawa, & Naoe, 2006; Y. Liu et al, 2017; Mamoori et al, 2017; Mascarello, Krous, & Carpenter, 1993). Besides identifying the abnormally expressed miRNAs in cancer cells, increasing studies currently aim at investigating the mechanisms involved for miRNAs to regulate cancer progression (Huang & Lu, 2017; Jin et al, 2017; X. Zhang, Li, Tan, Yu, & Pei, 2017). It has been widely accepted that miRNAs regulate cancer progression via targeting downstream genes to regulate their expression or translation, and one of the mechanisms involved is through targeting the transcription factors to regulate cell progressions (Cao, Yu, Feng, Chen, & Liang, 2017; W. Li, Liang, et al, 2017; Y. Li, Su, Li, Chen, & Zhang, 2017; Qiu & Dou, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found aberrantly lower-expression of miRNAs in colorectal tissues in contrast with normal tissues (Akao, Nakagawa, & Naoe, 2006;Mamoori et al, 2017;Mascarello, Krous, & Carpenter, 1993). Besides identifying the abnormally expressed miRNAs in cancer cells, increasing studies currently aim at investigating the mechanisms involved for miRNAs to regulate cancer progression (Huang & Lu, 2017;Jin et al, 2017;X. Zhang, Li, Tan, Yu, & Pei, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The above result suggests that miR‐30 may play a vital regulatory part during human cancer development. As discovered in our prior work, the expression of miR‐30b increases within RCC tissue samples, which may act as the oncogenic gene in RCC to regulate the proliferation of cells 13 . However, it remains unclear about whether miR‐30b‐5p can be used to be the candidate biomarker for predicting RCC prognosis.…”
Section: Introductionmentioning
confidence: 83%